2010
DOI: 10.1063/1.3510534
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of polydisperse spheres: Simulation strategies and an application to the freezing transition

Abstract: The statistical mechanics of phase transitions in dense systems of polydisperse particles presents distinctive challenges to computer simulation and analytical theory alike. The core difficulty, namely, dealing correctly with particle size fractionation between coexisting phases, is set out in the context of a critique of previous simulation work on such systems. Specialized Monte Carlo simulation techniques and moment free energy method calculations, capable of treating fractionation exactly, are then describ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 73 publications
(127 reference statements)
0
38
0
Order By: Relevance
“…Later, solid-fluid coexistence with fractionation was found in more realistic theory and simulation work for the experimentally relevant situation of a fixed overall size distribution. 18,22 Also, in theoretical and computational studies the coexistence of multiple solid phases was found, each with a narrow size distribution, in a system with a large overall polydispersity and a fixed overall size distribution. 18,21,23 It should be noted here that, when given enough time, a system can of course always divide itself up in less polydisperse subsystems that then may form crystal phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, solid-fluid coexistence with fractionation was found in more realistic theory and simulation work for the experimentally relevant situation of a fixed overall size distribution. 18,22 Also, in theoretical and computational studies the coexistence of multiple solid phases was found, each with a narrow size distribution, in a system with a large overall polydispersity and a fixed overall size distribution. 18,21,23 It should be noted here that, when given enough time, a system can of course always divide itself up in less polydisperse subsystems that then may form crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental systems the charge on the particles is affected by the local chemical potential of the charge-determining ions; the two limiting cases are described by assuming constant-charge or constant-potential boundary conditions on the particle surface. 12 For the case of hard spheres (or approximations thereof), phenomena arising from the presence of polydispersity have been investigated theoretically, [13][14][15][16][17][18][19][20][21][22][23] computationally 15,[21][22][23][24][25] and experimentally [26][27][28][29] (for a review see Ref. 11).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the second balance point 0' (1/2, -17/16) only occur on a part of thawed domains, which corresponding to the abnormal heat capacity and can be called as the abnormal or additional balance point at the GT. The additional attractive potential on point 0' comes from the self-similar fluctuation limit equation (14), or the recursion equation (6). …”
Section: Resultsmentioning
confidence: 99%
“…4, none of the potential curves, except for those who have passed, correspond with the stability condition of Eq. (14).…”
Section: F Fluctuation Stability Condition At Gtmentioning
confidence: 99%
See 1 more Smart Citation